Different frequencies of memory B-cells induced by tetanus, botulinum, and heat-labile toxin binding domains. (February 2019) - Rezaie, Ehsan; Nekoie, Hekmat; Miri, Ali; Oulad, Gholamreza; Ahmadi, Ali; Saadati, Mojtaba; Bozorgmehr, Mahmood; Ebrahimi, Marzieh; Salimian, Jafar
Abstract: Along with robust immunogenicity, an ideal vaccine candidate should be able to produce a long lasting protection. In this regard, the frequency of memory B-cells is possibly an important factor in memory B-cell persistency and duration of immunological memory. On this basis, binding domains of tetanus toxin (HcT), botulinum type A1 toxin (HcA), and heat-labile toxin (LTB) were selected as antigen models that induced long-term, midterm and short-term immune memory, respectively. In the present study, the frequency of total memory B-cells after immunization with HcT, HcA and LTB antigens after 90 and 180 days, and also after one booster, in 190 days, was evaluated. The results showed a significant correlation between frequency of total memory B-cells and duration of humoral immunity. Compared to other antigens, the HcT antibody titers and HcT total memory B-cell populations were greater and persistent even after 6 months. At 6 months after the final immunization, all HcT- and HcA-immunized mice survived against tetanus and botulinum toxins, and also LT toxin binding to GM1 ganglioside was blocked in LTB-immunized mice. We conclude the frequency of memory B-cells and their duration are likely a key factor for vaccine memory duration. Highlights: The relationship between antibody titers and memory B cells against the HcT, HcA, and LTB antigens is shown. The great difference was observed in the frequency of memory B-cells in respond to HcT, HcA, and LTB antigens. The sustained frequency of memory B cells was a critical factor in antigen-induced memory longevity.